(3hajGJ GdCYdGe ef GdTjYI GdcQGes - (3GdYGedj GdCUagGfj GdcGXej, CHh eMeO, MSf Hf gGOj Hf eMeO Ydj, J (B1354(3g`s ((3eTgO CejQ GdeDefjf Ydj Hf CHj WGdHs)
(3ChdgG (B:s
(3HSe Gddg (B... (3agPG eG SCdJ COGe Gddg Jhajbc aj JbjjO JGQjM Sfjf dhaGJ ef CYQa ef eTGgjQ YdeGA GdWHbI GdChdi GdEeGejI HJGQjN GdgLQI hPcQ YOI GYeGQge egeG Gecf hbO QJH Pdc Ydi WHbGJ YUhQ GdeGFI(B...s
(3BNQgG (B:s
... (3GdTjN CHh eMeO gGQhf Hf ehSi Hf CMeO Hf SYjO Hf SYO GdJdYcHQj GdTjHGfj cGf hGSY GdQhGjI Qhi LejY GdCUhd hGdeUfaGJ eGJ (B382 (3, GdTjN Ydj Hf eMeO Hf jYbhH (B.. (3Jes
(3efShNI Yf fSNI efShNI Yf fSNI efShNI Yf fSNI HNW GdeUfas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2/224s
(3GdPQjYI (B25 -79 ( 718 )s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJGQjNs